Mauriac Syndrome: A rare complication of tipe 1 Diabetes Mellitus – Case Report - Rivera Loaiza, Juan Pablo (2021)
Mauriac syndrome is a hepatic glycogenosis that occurs as a result of poorly controlled type 1 diabetes mellitus (DM1); has a major impact on the morbidity of diabetic patients. On this occasion, we will describe the case of a 14-year-old patient with a diagnosis of DM1, poor control of the disease and the presence of short stature, delayed pubertal development, elevated liver enzymes and cushingoid facies. The patient was treated with insulin at the appropriate dose for her weight, achieving metabolic control of the disease. With advances in the management of diabetes, this entity is less and less frequent, but it is important for healthcare personnel to know the pathology in order to make a timely diagnosis and to be able to make the appropriate therapeutic adjustment that can prevent the progression of the disease and the reversal of the established alterations.